A ANALISIS PENGARUH SIFAT FISIK DAN THERMAL LIMBAH FLY ASH BATUBARA DAN KAOLIN PADA PEMBUATAN FIRE BRICKS - Hidayat, Randy; Putri, Fenoria; Karmin, Karmin (MACHINERY Jurnal Teknologi Terapan, 2025)
The increase in coal waste (fly ash and bottom ash) will have a negative impact on the environment if it is not managed or utilized. One of the uses of coal waste can be used as a mixture for making refractory bricks. Refractory bricks are made with a variety of materials with the fixed variable composition being 30% clay and 10% alumina and the independent variables FA and Kaolin waste with variations of 20%:40%, 30%:30%, 40%:20%. Samples of refractory bricks that has been made is tested by Density & Porosity Test, Compressive Strength Test, and Heat Conductivity Test. The results were obtained in the density and porosity tests on the 30% fly ash variation with sequential values of 1.782 gr/cm3 and 42.419%, as well as compressive strength of 7.24 N/mm2 and the highest thermal conductivity on the 20% fly ash variation with a value of 1.773 W/m.oK